Maize dispersal patterns associated with different types of endosperm and migration of indigenous groups in lowland South America. (27th April 2022) - Costa, Flaviane Malaquias; Silva, Natalia Carolina de Almeida; Vidal, Rafael; Clement, Charles Roland; Freitas, Fabio de Oliveira; Alves-Pereira, Alessandro; Petroli, César Daniel; Zucchi, Maria Imaculada; Veasey, Elizabeth Ann
Abstract: Background and Aims: The lowlands of South America appear to be remarkably important in the evolutionary history of maize, due to new evidence that suggests that maize dispersed from Mexico and arrived in this region in a state of partial domestication. This study aimed to identify dispersal patterns of maize genetic diversity in this part of the continent. Methods: A total of 170 maize accessions were characterized with 4398 single nucleotide polymorphisms (SNPs) and analysed to determine if maize dispersal was associated with types of endosperm and indigenous language families. Key Results: Four genetic groups were identified in the discriminant analysis of principal components and five groups in the cluster analysis (neighbour-joining method). The groups were structured according to the predominance of endosperm types (popcorn, floury, flint/semi-flint). Spatial principal component analysis of genetic variation suggests different dispersal patterns for each endosperm type and can be associated with hypotheses of expansions of different indigenous groups. Conclusions: From a possible origin in Southwestern Amazonia, different maize dispersal routes emerged: (1) towards Northern Amazonia, which continued towards the Caatinga and south-eastern Atlantic Forest (Floury); (2) towards Southern Brazil, passing through the Cerrado and Southern Atlantic Forest reaching the Pampa region (Floury); and (3) along the Atlantic Coast, following Tupi movements originating from two separate expansions: one (Tupinamba) from north to south, and the other (Guarani) in the opposite direction, from south to north (flint, floury and popcorn).